Ajaran Martabat Tujuh di dalam Kepustakaan Jawa - Suwarno Imam S. (Refleksi: Jurnal Kajian Agama dan Filsafat, 2004)
This text discusses the teachings of the Seven Degrees within Javanese literature. The study is based on two sources, namely the Javanese version of Tuhfah written around 1680, and Serat Centini written in the early 19th century. The Seven Degrees doctrine in Javanese literature is presented in the form of poems containing terms related to the seven degrees, such as Ahadiyah, Wahdah, Wahidyah, la ta’yun, and the essence of Muhammadiyah. However, the terms used in Serat Centini have undergone slight changes, both in the spelling of certain letters and specific words. This is associated with the passage of time, allowing for the influence of Javanese culture.